Pengaruh Pelatihan Mandiri Menggunakan Platform Merdeka Mengajar Terhadap Kompetensi Guru Di SMA Negeri 21 Makassar - St Rahma; Muhammad Azis; M. Ridwan Tikollah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the influence of independent training using the Merdeka teaching platform on teacher competence at SMA Negeri 21 Makassar. The variables of this study are independent training using the Merdeka teaching platform as an independent variable (X) and teacher competence as a bound variable (Y). The population of this study is all teachers at SMA Negeri 21 Makassar which totals 79 teachers, while the sample in this study uses a purposive sampling technique with the criteria of teachers who have an belajar.id account and use the Merdeka teaching platform and use the independent training feature with a sample of 50 teachers. The data collection techniques used are questionnaires and documentation. The data analysis techniques used are descriptive statistical analysis, instrument tests and hypothesis tests using SPSS 25 for windows. The results of this study indicate that: (1) Based on the results of descriptive statistical analysis, independent training using the Merdeka Mengajar platform of 81 percent is included in the very good category and teacher competence of 86 percent is included in the very good category. (2) Based on the results of a simple linear analysis, independent training using the Merdeka Mengajar platform was obtained Y = 58.662 + 0.370X, which means that for every additional value of independent training, the teacher competence value increases by 0.370. 3) From the results of the t-test analysis, the significance value of 0.000 <0.05 means that the independent training variable has a positive and significant effect on teacher competence in teachers of SMA Negeri 21 Makassar, thus the hypothesis is "accepted". (4) From the results of the determination coefficient (KD) analysis, the R2 value was obtained = 26.9 percent and the remaining 73.1 percent was influenced by other factors.